Modeling mechanical performance of lightweight concrete containing silica fume exposed to high temperature using genetic programming - Tanyildizi, Harun; Cevik, Abdulkadir (Elsevier Sci Ltd, 2010)
In this study, the mechanical performance of lightweight concrete exposed to high temperature has been modeled using genetic programming. The mixes incorporating 0%, 10%, 20% and 30% silica fumes were prepared. Two different cement contents (400 and 500 kg/m(3)) were used in this study. After being heated to temperatures of 20 degrees C, 200 degrees C, 400 degrees C and 800 degrees C, respectively, the compressive and splitting tensile strength of lightweight concrete was tested. Empirical genetic programming based equations for compressive and splitting tensile strength were obtained in terms of temperature (T), cement content (C), silica fume content (SF), pumice aggregate content (A), water/cement ratio (W/C) and super plasticizer content (SP). Proposed genetic programming based equations are observed to be quite accurate as compared to experimental results. (C) 2010 Elsevier Ltd. All rights reserved.
5th Kumamoto International Workshop on Fracture, Acoustic Emission and Nondestructive Evaluation in Concrete (KIFA-5) -- SEP 17-18, 2009 -- Kumamoto, JAPAN
Keywords: Lightweight concrete; Silica fume; High temperature; Mechanical properties; Genetic programming